81.6k views
3 votes
Someone help please:)

Someone help please:)-example-1

2 Answers

6 votes

Answer:

43 - 2x = 12x +1

43 - 1 - 2x = 12x + 1 - 1

42 - 2x = 12x

42 - 2x + 2x = 12x + 2x

42 = 14x

42 / 14 = 14x / 14

x = 3

WY = 43 - 2(3)

WY = 37

Explanation:

1. since both segments from the same external point are tangent, they are congruent, so we can set them equal to each other.

2. subtract one from both sides

3. subtract two from both sides

4. divide to get the variable itself.

5. take the length of WY and replace x by its value to find the measure of WY.

User DGuntoju
by
4.8k points
4 votes

Answer:

37

Explanation:

Our equation: 43 - 2x = 12x + 1

  1. Add 2x to both sides: 43 = 14x + 1
  2. Subtract 1 from both sides: 42 = 14x
  3. Divide 14 from both sides: 3 = x
  4. Replace x with 3 in the expression that is equal to WY: 43- 2(3)
  5. Solve using PEMDAS
  6. 37 is our answer

User Mppfiles
by
4.9k points